Designing Teaching Process for Stem Topic “Traffic Signal Lights” for Upper-secondary School Students - Huy, Tran Quang; Khanh, Pham Quoc; Van Anh, Khuc Thi; Thong, Nguyen Duc; Hieu, Tran Trung; Quynh, Le Khac; Tuan, Nguyen Ngoc; Thu, Nguyen Van (VNU Journal of Science: Education Research; Vol 38 No 2, 2022)
In this paper, we propose a new STEM topic in the automation field for upper-secondary school students, which is the topic "Traffic signal lights". This STEM education is designed to be relevant to the current general education curriculum in subjects as Physics, Technology, and Informatics. Based on the 6E learning model, the teaching process is built for this topic, in which two factors of technical design and practice (programming and assembly of circuits) are emphasized in STEM-oriented teaching for upper-secondary school students.